A recombinant conjugated pneumococcal vaccine that protects against murine infections with a similar efficacy to Prevnar-13. (December 2018) - Reglinski, Mark; Ercoli, Giuseppe; Plumptre, Charlie; Kay, Emily; Petersen, Fernanda; Paton, James; Wren, Brendan; Brown, Jeremy
Abstract The pneumococcal conjugate vaccine (PCV) strongly protects against vaccine serotypes, but the rapid expansion of non-vaccine serotype disease and the vaccine's high expense has reduced its overall impact. We have developed Protein Glycan Coupling Technology (PGCT) as a flexible methodology for making low-cost polysaccharide/protein glycoconjugates recombinantly inEscherichia coli . We have used PGCT to make a recombinant PCV containing serotype 4 capsular polysaccharide linked to theStreptococcus pneumoniae proteins NanA, PiuA, and Sp0148. The introduction of theCampylobacter jejuni UDP-glucose 4-epimerase gene GalE (gne ) intoE. coli improved the yield of the resulting glycoprotein. PGCT glycoconjugate vaccination generated strong antibody responses in mice to both the capsule and the carrier protein antigens, with the PiuA/capsule glycoconjugate inducing similar anti-capsular antibody responses as the commercial PCV Prevnar-13. Antibody responses to PGCT glycoconjugates opsonisedS. pneumoniae andStreptococcus mitis expressing the serotype 4 capsule and promoted neutrophil phagocytosis ofS. pneumoniae to a similar level as antisera generated by vaccination with Prevnar-13. Vaccination with the PGCT glycoconjugates protected mice against meningitis and septicaemia with the same efficacy as vaccination with Prevnar-13. In addition, vaccination with the protein antigen components from PGCT glycoconjugates alone provided partial protection against septicaemia and colonisation. These data demonstrate that a vaccine made by PGCT is as effective as Prevnar-13, identifies PiuA as a carrier protein for glycoconjugate vaccines, and demonstrates that linking capsular antigen toS. pneumoniae protein antigens has additional protective benefits that could provide a degree of serotype-independent immunity. Pneumococcal vaccines: evaluation of a multivalent pneumococcal glycoconjugate vaccine The current pneumococcal conjugate vaccine induces protective immunity to infection, but this protection is limited to the dominant disease-causing strains included in the preparation. Emerging strains not included in the vaccine are not covered, which limits the vaccine's protective effect in areas associated with alternative pneumococcal strains. Here Jeremy Brown, Brendan Wren and colleagues have optimised and applied Protein Glycan Coupling Technology to produce recombinant pneumococcal polysaccharide/protein glycoconjugates and evaluated these in a murine model of infection. Glycoconjugate vaccination resulted in antibody production specific to both capsule and the carrier proteins, which resulted in protection in murine models of meningitis and septicaemia equivalent to that of currently used vaccination strategies. This animal study highlights the potential of glycoconjugate vaccine approaches in the context of pneumococcal mediated disease.